Frequency of Common Bacteria and Antibiotic Sensitivity in Patients with Indwelling Catheter Associated Urinary Tract Infections - Muhammad Ayaz, Shaheer Ahmad Khan, Muhammad Daud Khalil, Salman Khan, Syed Jalal Shah, Naqeeb Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Examine the prevalence of common bacteria and their antibiotic susceptibility in individuals with urinary tract infections caused by indwelling catheters. Study Design: Cross-sectional descriptive research. Place and Duration of study: From January 30, 2021, to July 29, 2021, researchers from the Department of Medicine at Muhammad Teaching Hospital in Peshawar, collected data for this study. Materials and Methods: The proportion of patients with Enterococcus spp. urinary tract infections2 was 5.4%, with a 95% confidence interval and a 3.5% margin of error using WHO software, and they monitored 179 individuals. In addition, a non-probabilistic sampling method based on a sequence of samples was applied. Results: Based on our data, the median age was 47 years old (with a standard deviation of ±2.15), and 33% of our participants were male and 67% were female. Escherichia coli was detected in 37% of patients with catheter linked urinary tract infection, Staphylococcus epidermidis in 18%, Pseudomonas aeruginosa in 16%, Klebsiella pneumonia in 20%, Proteus mirabilis in 3%, and Enterococcus in 6%. Conclusion: Escherichia coli (37%) was the most prevalent bacterium found in catheter-associated urinary tract infections, followed by Klebsiella pneumonia (20%), Staphylococcus epidermidis (18%), and Pseudomonas aeruginosa (16 percent). Keywords: Infection of the urinary tract caused by a catheter, urinary catheterization, CAUTI. E. coli, microorganisms, antibiotics, and infectious diseases.